Redescriptions and species status of the South African mites Galumna lawrencei Jacot, 1940 and Galumna natalensis Jacot, 1940 (Acari, Oribatida, Galumnidae), with lectotype designation - Ermilov, Sergey G.; Hugo-Coetzee, Elizabeth A. (Zootaxa, 2019)
The main morphological traits of Galumna lawrencei Jacot, 1940 stat. nov. and Galumna natalensis Jacot, 1940 stat. nov. (Oribatida, Galumnidae) are presented based on the type material from South Africa. We consider that these species are not subspecies of Galumna maxima as was proposed originally by Jacot 1940, but independent species. A lectotype for G. lawrencei is designated, due to the mixed-species cotype series.